Training on Introduction to Climate Information Services for Agriculture Module: Training Evaluation Report - Ekepu, David; Nakayiwa, Florence; Majaliwa, Mwanjalolo; Hansen, Jim; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate information services (CIS) are critical for making important decisions in agriculture in order to assess and manage risks associated with climate change and climate variability. The partnership between RUFORUM and IRI aims to develop and increase accessibility of climate information services curricula for training in African universities as well as ensure utilization of among key stakeholders in agriculture such as extension workers and farmers. The CIS for agriculture is piloted to increase awareness and adoption of climate relevant curricula in African Universities.